Discovery of a new species of the brachyelytrous net-winged beetle genus Alyculus (Coleoptera: Lycidae) from Peninsular Malaysia - Takahashi, Naoki; Bocak, Ladislav; Ghani, Idris Abd. (Zootaxa, 2016)
The net-winged beetle genus Alyculus Kasantsev is reported from Peninsular Malaysia for the first time and a new species, A. malaypeninsularis sp. nov., is described and illustrated. An expanded identification key to Alyculus males is provided and the biology and distribution of the species are discussed.